The Effect of Water Treatment Models to Reduce Lead (Pb) Level on Freshwater Snail Filopaludina javanica - Arfiati, Diana; Syahid, Nur; Anwari, Zaki; Aminin, Aminin; Kusriani, Kusriani; Herawati, Endang Yuli; Puspitasari, Asthervina Widyastami (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Lead is a kind of non-essential heavy metals included in the metal causing environmental pollution with persistent properties that might harm the consumers. This study aimed to determine the best method for reducing the lead level on the freshwater snail Filopaludina javanica using three various water treatment models. Soaking water treatment (6h, 12h, 18h, 24h), flowing water treatment (6h, 12h, 18h, 24h), and refreshing water treatment (6h, 12h, 24h). The lead level assay in both samples used Atomic absorption spectroscopy (AAS), and the physical and chemical parameters were measured, such as temperature, pH, and Dissolved Oxygen (DO). The lowest value of lead content on freshwater’s soft body snail and water sample respectively were soaking water treatment at 6h (0.64 ± 0.02 mg L-1) and 24h (0.0045 ± 0.0015 mg L-1); flowing water treatment at 24h (0.04 ± 0.007 mg L-1) and 18h (0.0036 ± 0.0009 mg L-1) and; refreshing water treatment at 24h (0.150 ± 0.011) and 12h (0.007 ± 0.001), with control 0.072 ± 0.00 mg L-1 and 0.067 ± 0.00 mg L-1. Therefore, the most effective model to reduce the lead content was flowing water treatment within 24h in the freshwater soft body snail and 18h in the water sample.